Survey of heating and current drive for K-DEMO. (22nd January 2018) - Mikkelsen, D.R.; Kessel, C.E.; Poli, F.M.; Bertelli, N.; Kim, K.
Abstract: We present calculations of heating and current drive by neutral injection and by electromagnetic waves in the ion cyclotron, helicon, lower hybrid, and electron cyclotron frequency ranges for the steady state burn conditions in a K-DEMO configuration with I p = 12.3 MA, a   =  2.1 m, R o = 6.8 m, B o = 7.4 T, n ̄ e = 1.1 × 10 20 m −3, T ( 0 ) = 40 keV, and Z e f f = 1.5 . Lower hybrid wave current drive calculations comprise a 2D scan over poloidal launcher location and launched n ∥, at a fixed frequency of 5 GHz. An ICRF frequency scan over 50–100 MHz is based on an ITER-like ICRF midplane antenna; the absorption calculation includes thermal D, T, He, Ar, and W as well as suprathermal beam ions and alphas. Helicon fast wave performance is surveyed by varying frequency over 0.6–2.5 GHz, launched n ∥ from  −1.6 to  −3, and launcher position from top to bottom on the low-field side. An ITER-like 1 MeV neutral beam system with quasi-tangential geometry is scanned over elevation to vary the targeted minor radius. The electron cyclotron survey varies the frequency (190–300 GHz), launcher poloidal location, and the poloidal and toroidal direction of the launched waves. We report for each system the range of minor radius in which current is driven, the current drive efficiency, the optimal system parameters, and typical profiles of driven current. Electron and ion heating profiles are reported for the ICRF and NBI systems.